ANALISA PENGARUH MATAKULIAH KEWIRAUSAHAAN TERHADAP MINAT WIRAUSAHA MAHASISWA STMIK SINAR NUSANTARA - Bambang Satrionugroho, Didik Nugroho (Jurnal Ilmiah SINUS, 2015)
Entrepreneurship learning in college, it is a duty to be implemented. Because the government is keen to foster the entrepreneurial spirit of students, so that they can be free from dependence with others.The purpose of this study was to determine the effect of entrepreneurship courses on student interest to become entrepreneurs. The background of this research will about how the influence of entrepreneurship courses in the interest of students to become entrepreneurs. The sampling technique used was purposive sampling and data collecting by using a questionnair, inference analysis using linear regression .. The number of respondents who were taken by, 60 respondents. The results of this study, learning materials entrepreneurship courses, apparently affect the overall interest of students to become entrepreneurs by 41.8%, while 58.2 % are influenced by other factors not examined. This study is also looking for material that needs to be given to entrepreneurship subjects that really support the increased interest in entrepreneurship, in the form of teaching materials Entrepreneurship courses, especially in information technology Keywords : Entrepreneurship, Entrepreneurial Interests